A revision of the Devonian Malvinokaffric dalmanitid trilobite Dalmanitoides Delo, 1935, on the basis of new data from Argentina - Rustán, Juan José (2012)
In light of new information on holotypes and additional material from the Lower Devonian type areas from Argentina, the dalmanitid trilobite Dalmanitoides Delo, 1935,is rediagnosed and considered a dalmanitine rather than a synphoriine. Comparison ssuggest that Gamonedaspis Braniša and Vaněk, 1973, is a junior synonym of Dalman-itoides, so that this Early-Middle Devonian genus includes at least five species: fourformally named from South America, D. drevermanni (Delo, 1935), D. boehmi (Knod,1908), D. scutata (Braniša and Vaněk, 1973), and D. accola (Clarke, 1913), together with a species from South Africa here in treated in open nomenclature (D. sp. A).Although the number of Dalmanitoides species suggests a diversification of cosmopol-itan dalmanitines already present in Malvinokaffric basins, a close relationship with the boreal and slightly older Roncellia Lespérance and Bourque, 1971, would suggest migration from the Eastern Americas Paleobiogeographical Realm during the EarlyDevonian as origin of the clade, which is in accordance with paleobiogeographic pat-terns recognized on the basis of evidence from synphoriine distributions.